2004
DOI: 10.1111/j.1365-2966.2004.07450.x
|View full text |Cite
|
Sign up to set email alerts
|

LX-SFR relation in star-forming galaxies

Abstract: We compare the results of Grimm, Gilfanov & Sunyaev and Ranalli, Comastri & Seti on the L X -SFR (X-ray luminosity-star formation rate) relation in normal galaxies. Based on the L X -stellar mass dependence for low-mass X-ray binaries (LMXBs), we show that low-SFR ( 1 M yr −1 ) galaxies in the Ranalli et al. sample are contaminated by the X-ray emission from LMXBs, unrelated to the current star formation activity.However, the most important conclusion from our comparison is that, after the data are corrected f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
172
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(188 citation statements)
references
References 13 publications
16
172
0
Order By: Relevance
“…In particular, high-mass X-ray binaries (HMXBs) are considered to be the dominant source for the X-ray emission above 2 keV. A good correlation between the 2-10 keV luminosity and the star formation rate have been found for nearby star forming galaxies (Ranalli et al 2003;Grimm et al 2003;Gilfanov et al 2004) as well as for late type galaxies at higher redshift (Lehmer et al 2008). The galacticscale emission nebulae, traced by Hα and the soft X-ray emission in local starburst galaxies like M 82, suggested that these extended nebulae are produced by the shock heated interstellar medium, swept up by a starburst-driven outflow (see e.g., Notes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, high-mass X-ray binaries (HMXBs) are considered to be the dominant source for the X-ray emission above 2 keV. A good correlation between the 2-10 keV luminosity and the star formation rate have been found for nearby star forming galaxies (Ranalli et al 2003;Grimm et al 2003;Gilfanov et al 2004) as well as for late type galaxies at higher redshift (Lehmer et al 2008). The galacticscale emission nebulae, traced by Hα and the soft X-ray emission in local starburst galaxies like M 82, suggested that these extended nebulae are produced by the shock heated interstellar medium, swept up by a starburst-driven outflow (see e.g., Notes.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between X-ray and radio luminosities of star forming galaxies, and between the X-ray and FIR ones, are well established for the local universe and have been tested for objects up to z ∼ 1 RCS03;Gilfanov et al 2004a;Persic & Rephaeli 2007). Both the radio and FIR luminosity are tracers of the star formation rate (SFR).…”
Section: The X-ray/radio Flux Ratiomentioning
confidence: 99%
“…The X-ray domain has also been recognized as a SF tracer in non-active galaxies (hereafter just "galaxies") thanks to a number of works highlighting the presence of X-ray vs. radio/infrared correlations (David et al 1992;Grimm et al 2003;Ranalli et al 2003, hereafter RCS03;Gilfanov et al 2004a). Strong absorption (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these stars will be HMXB secondaries: Indeed several studies of late-type galaxies have established strong correlations between galaxy-wide X-ray luminosity and total SFR (e.g., Bauer et al 2002;Grimm et al 2003;Ranalli et al 2003;Gilfanov et al 2004a;Persic et al 2004;Hornschemeier et al 2005;Persic & Rephaeli 2007;Lehmer et al 2008Lehmer et al , 2010Mineo et al 2012). On the other hand, in quiescent (morphologically elliptical/S0) galaxies, longer-lived (1 Gyr) low-mass stars trace the total stellar mass accumulated over a galaxy's lifetime.…”
Section: Introductionmentioning
confidence: 99%